2013
DOI: 10.1021/bi400804z
|View full text |Cite
|
Sign up to set email alerts
|

MscS-like Mechanosensitive Channels in Plants and Microbes

Abstract: The challenge of osmotic stress is something all living organisms must face as a result of environmental dynamics. Over the past three decades, innovative research and cooperation across disciplines has irrefutably established that cells utilize mechanically gated ion channels to release osmolytes and prevent cell lysis during hypoosmotic stress. Early electrophysiological analysis of the inner membrane of Escherichia coli identified the presence of three distinct mechanosensitive activities. The subsequent di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 163 publications
2
63
0
Order By: Relevance
“…As a result, we and others have previously speculated that the topological and domain diversity associated with MscS homologs indicates a multiplicity of functions and regulatory mechanisms and further proposed that MscS homologs might serve as membrane tension sensors with outputs independent of ion flux Wilson et al, 2013;Cox et al, 2014). Here, we present a structural and functional analysis of Arabidopsis MSL10 that supports these ideas.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…As a result, we and others have previously speculated that the topological and domain diversity associated with MscS homologs indicates a multiplicity of functions and regulatory mechanisms and further proposed that MscS homologs might serve as membrane tension sensors with outputs independent of ion flux Wilson et al, 2013;Cox et al, 2014). Here, we present a structural and functional analysis of Arabidopsis MSL10 that supports these ideas.…”
Section: Introductionsupporting
confidence: 69%
“…Homologs of MscS are found in nearly all bacterial species (Pivetti et al, 2003;Lai et al, 2013;Martinac et al, 2013), protozoa (Prole and Taylor, 2013), archaea (Palmieri et al, 2009), some fungi (Nakayama et al, 2012), and all plant genomes so far analyzed (Wilson et al, 2013) but have not been identified in animals. The region of sequence similarity between MscS and other members of the MscS superfamily is restricted to a relatively small portion of the protein that includes the pore-lining helix of MscS and ;100 amino acids of the upper cytoplasmic domain (Kloda and Martinac, 2002;Pivetti et al, 2003;Balleza and Gómez-Lagunas, 2009;Haswell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant effects were observed in the higher-order mechanosensitive Ca 2+ channel root Mid1-complementing activity mca1;mca2 (AT4G35920, AT2G17780) double mutant (34,35) or the plasma membrane-targeted members of the mechano-sensitive channel of small conductance (MscS)-like family msl4,5,6,9,10 (AT1G53470, AT3G14810, AT1G78610, AT5G19520, AT5G12080) quintuple mutant ( Fig. S4) (36). Additionally, it has been shown previously that the tpc1 (AT4G03560) mutants in the vacuolar Ca 2+ -activated Ca 2+ -permeable SV channel do not affect the rapid osmotically induced increase in Ca 2+ but rather impair the ensuing root-to-shoot Ca 2+ wave (12).…”
Section: Survey Of Ion Transporters That May Play a Role In Elicitingmentioning
confidence: 99%
“…Although MscS is a non-specific channel, other members of this family are ligand-specific and some of them are hypothesised not to be channel proteins at all, which explains the plurality of MscS-like proteins in a species (Gibson et al, 2015;Wilson et al, 2013).…”
Section: Overview Of Mscs-family Of Proteinsmentioning
confidence: 99%